Pengaruh Pembiasaan Keteladanan Terhadap Perilaku Disiplin Pada Anak PAUD Kelompok B - Munira Abdul Rauf; Us Djuko, Rapi; Utoyo, Setiyo (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
This study aimed to obtain the data that concerned the effect of moral habituation on disciplinary behavior towards children. Quantitative data was employed using the design intact-group comparison as the research method. The study depicted that there was no effect on the previously mentioned study towards children’s disciplinary behavior, and it can be seen from the children’s disciplinary post-test average score, which was between 0.572 and 573. The result proves that the there is no significant influence on the development of disciplinary behavior in children.